Advertising Exposure: A Review on Advertising Challenges in Digital Era. - Gunarathne, Inoka (Archives of Business Research, 2019)
Digital advertising have changed the landscape of advertising in the digital era. Yet, getting the viewers’ attention to advertisement in both traditional and digital forms is a constant challenge for advertisers. There are limited studies being conducted on the notion of effect of social contact and interaction, and it is not known as to what contributes to the relationship between social interactions and internet advertisement attitudes. While there are many optimistic indicators in digital advertising, decreasing click through rates, confusion concerning suitable advertising pricing models, and uncertainty regarding whether traditional advertising metrics are appropriate for new media like the internet, are contributing to increasing skepticism regarding the value of digital advertising. Thus, the objective of this paper is to contribute to the existing knowledge in the field of advertising exposure. Accordingly, this paper followed deductive approach to review the literature in relation to exposure impact of advertising content with special reference to use of language and the photographs of expressions in advertisements. Finally, this paper concludes the future research priorities on the advertising in digital era.